Menstrual phase influences cerebrovascular responsiveness in females but may not affect sex differences - Skinner, B. D.; Weaver, S. R. C.; Lucas, S. J. E.; Lucas, R. A. I. (Frontiers in Physiology, 2023)
Background and aims: Sex differences in the rate and occurrence of cerebrovascular diseases (e.g., stroke) indicate a role for female sex hormones (i.e., oestrogen and progesterone) in cerebrovascular function and regulation. However, it remains unclear how cerebrovascular function differs between the sexes, and between distinct phases of the menstrual cycle. This study aimed to compare cerebrovascular-CO2 responsiveness in 1) females during the early follicular (EF), ovulatory (O) and mid-luteal (ML) phases of their menstrual cycle; and 2) males compared to females during phases of lower oestrogen (EF) and higher oestrogen (O).